Limit groups, positive-genus towers and measure equivalence - Bridson, M; Tweedale, M; Wilton, H (2005)
By definition, an $ω$-residually free tower is positive-genus if all surfaces used in its construction are of positive genus. We prove that every limit group is virtually a subgroup of a positive-genus $ω$-residually free tower. By combining this with results of Gaboriau, we prove that elementarily free groups are measure equivalent to free groups.